TL 18091 - Risk in the sinus tarsi approach: an anatomical study - Heitzmann, Lourenço Galizia; Molina, Wellington Farias; Martins, Guilherme Bottino; Pimenta, Luiz Sergio Martins; Alvo, Fernando Salgueiro; Capellasso, Bruno Augusto Mendonça (Scientific Journal of the Foot & Ankle, 2019)
Objetivo: To evaluate the topographic and morphometric aspects of the sural nerve in cadavers as well as its relationship with the modified Palmer approach. Methods: Thirty lower limbs of fifteen fresh cadavers were used for dissection of the sural nerve, and 5 measurements were performed using the lateral malleolus and the calcaneal tendon as the repair point. The paired student’s T-test was used to compare the averages of the measurements between the sides of the same cadaver. A value of p < 0.05 was considered significant for all analyses. Results: On average, the sural nerve issued its first branch 40.40 mm above the lateral malleolus, situated on average 13.84 mm posterior to the tip of the lateral malleolus and on average 23.76 mm inferior to the point of the lateral malleolus. Conclusion: The modified Palmer’s approach was shown to be promising, since it demonstrated lower postoperative complication rates, especially when compared with the extended lateral pathway. The results obtained will aid during the surgical incision, adding safety to the procedure by avoiding injury of branches of the sural nerve.